Kedisiplinan, Kompetensi Dan Motivasi Terhadap Kinerja Pegawai Pada Tiga Kantor Kecamatan Di Kabupaten Maros - Hermin Andi Magga; Mahmud Mahmud (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
The purpose of this study was to determine the Effect of Discipline, Competence and Motivation on Employee Performance in Three District Offices in Maros Regency. The population in this study were employees at three district offices in Maros who were random, where the sample was 51 employees. The analysis method used is multiple linear regression.The results showed that simultaneously all independent variables consisting of discipline, competence, and motivation have a positive and significant effect on employee performance in three sub-district offices in Pangkep Regency. Partially the independent variables of discipline and motivation have a positive and significant effect, while the independent variable of competence has no positive and significant effect.